The edge of the blade - Kennedy, Jeffe, 1966- (Kennedy, Jeffe, 1966- Uncharted realms., 2017)
The ease and grace that come to Jepp naturally in fighting leathers disappears when battles turn to politics. When a scouting party arrives from far-away Dasnaria, bearing veiled threats and subtle bluffs, Jepp is happy to let her queen puzzle them out while she samples the pleasures of their prince's bed. But Jepp's light use of Prince Kral has sparked a diplomatic crisis. Banished from court, she soon becomes the only envoy to Kral's strange and dangerous country, with little to rely on but her wits, her knives-- and the smolder of anger and attraction that burns between them....